PENGARUH INVESTASI DAN PERKEMBANGAN TEKNOLOGI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Hanim, Anifatul; Hermawan, Gilang Brata; Wilantari, Regina Niken (Jurnal Penelitian Sains dan Teknologi Indonesia, 2022)
Economic growth is an indicator to show the economic performance and economic development of a country. Economic growth theory has many figures with it thoughts. One of them is Solow's thinking, which considers that investment and technology can drive economic growth. Harrod Domar also state that investment can boost economic growth. The purpose of this study is to analyze the effect of Foreign Direct Investment (FDI), Domestic Direct Investment (DDI), and the ICT Index on Indonesia's economic growth. The method used in this research is Least Square Panel (PLS). The results showed that the Domestic Direct Investment (DDI) and the ICT Index had a positive and significant effect on Indonesia's economic growth. In contrast to these two variables,  Foreign Direct Investment (FDI) has a positive but insignificant effect on Indonesia's economic growth.